Morphology and phylogenetic analyses reveal Neopalmiascoma gen. nov. (Bambusicolaceae, Pleosporales) on Macadamia integrifolia in Yunnan Province, China - Zhang, Xian; Karunarathna, Samantha C.; Saowaluck Tibpromma,; Du, Tian-Ye; Elgorban, Abdallah M.; Lumyong, Saisamorn; Dong-Qin Dai,; Hyde, Kevin D. (Phytotaxa, 2024)
Macadamia integrifolia, one of the cash crops widely grown in the tropical and subtropical regions produces edible kernels with high oil content. Several fungal pathogens have been reported from this host, but very few studies on saprobic fungi have been carried out. As a part of our studies on saprobic fungi of edible nuts, dead branches of Macadamia integrifolia with fungal fruiting bodies were collected from Yunnan Province of China. Molecular analyses of combined SSU, ITS, LSU, RPB2, and TEF1-α sequence data showed that our collection belongs to Bambusicolaceae and forms a distinct branch with other genera in this family. Our collection fits well with the Bambusicolaceae, and morphology is similar to Palmiascoma but can be distinguished by molecular data. Therefore, we introduce our collection as Neopalmiascoma gen. nov., with N. macadamiae as the type species. A description, photo plate, and phylogenetic tree to show the taxonomic placement of the new species are provided.